Integrated Intelligence Practice to Motivate Low Achievement Students in the History Subject - Ahmad, Abdul Razaq; Sulaiman, Fadzilah (SUSURGALUR, 2015)
ABSTRACT: The teachers were expected to apply a new approach with various teaching activities to motivate students to learn. The sample consisted of 68 low achieversâ students, who were then divided into two groups: 34 students were treated in the treatment group, while another 34 students were put in the control group. This is a quasi-experiment of non equivalent control group design. The questionnaire was distributed to students of both groups, to test the effectiveness of the integration approach. Analysis of the mean and standard deviation was conducted for both groups, while the null hypothesis was tested by the t-test. Based on the pre-test, there was no significant difference between the two groups. The post-test recorded significant motivational differences between the two groups studied. It was determined that the integrated History lesson with multiple intelligences had increased the level of motivation among students in the treatment group. This shows, that diversity of methods and activities undertaken, were able to change studentsâ perception about the History subject and had increased their interests to learn History. Hence, integrated multiple intelligence activities are able to increase students motivation to learn the History.KEY WORD: Integrated multiple intelligence, studentsâ motivation, readiness to learn, history subject, new approach, and teachersâ teaching practices.IKHTISAR: âAmalan Kecerdasan Bersepadu untuk Memberi Motivasi kepada Pelajar-pelajar Berpencapaian Rendah dalam Subjek Sejarahâ. Guru-guru diharapkan dapat melaksanakan pendekatan baru melalui aktiviti yang pelbagai bagi memberi dorongan kepada pelajar untuk belajar. Sampel yang terlibat terdiri daripada 68 orang pelajar berpencapaian rendah, yang dibahagikan kepada dua kumpulan, iaitu: 34 orang pelajar kumpulan rawatan serta 34 orang lagi pelajar kumpulan kawalan. Kajian ini berbentuk kuasi eksperimen kumpulan tidak setara. Bagi menguji keberkesanan integrasi teori kecerdasan pelbagai, soal selidik digunakan ke atas pelajar dari kedua-dua kumpulan. Analisis min dan sisihan piawai digunakan ke atas kedua-dua kumpulan, manakala bagi menguji hipotesis nul, ujian t digunakan. Berdasarkan ujian pada peringkat pra, tidak terdapat perbezaan yang signifikan antara kedua-dua kumpulan. Dalam ujian pada peringkat pos pula terdapat perbezaan motivasi belajar antara kedua-dua kumpulan. Didapati bahawa pengajaran bersepadu dengan kecerdasan pelbagai telah meningkatkan faktor dorongan dalam kalangan pelajar kumpulan rawatan. Hal ini menunjukkan kepelbagaian kaedah dan aktiviti yang dilaksanakan telah dapat mengubah persepsi pelajar tentang mata pelajaran Sejarah serta meningkatkan kesediaan mereka untuk belajar Sejarah. Oleh itu, aktiviti kecerdasan pelbagai bersepadu dapat meningkatkan dorongan pelajar untuk belajar Sejarah.KATA KUNCI: Kecerdasan pelbagai bersepadu, dorongan pelajar, sedia untuk belajar, mata pelajaran sejarah, pendekatan baru, dan amalan pengajaran guru.Â Â Â About the Authors: Assoc. Prof. Datoâ Dr. Haji Abdul Razaq Ahmad and Fadzilah Sulaiman are the Lecturers at the Faculty of Education UKM (National University of Malaysia), Bangi, Selangor Darul Ehsan, Malaysia. For academic interests, the authors can be contacted via e-mail at: razaq.ukm@gmail.com How to cite this article? Razaq Ahmad, Abdul & Fadzilah Sulaiman. (2015). âIntegrated Intelligence Practice to Motivate Low Achievement Students in the History Subjectâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.3(1), Maret, pp.57-70. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808. Â Chronicle of the article: Accepted (December 18, 2014); Revised (January 25, 2015); and Published (March 24, 2015).